TOOLS OF INTRA-UNIVERSITY MECHANISM OF IMPROVING THE EDUCATIONAL SERVICE - E. A. Kotlyarova (Russian Journal of Economics and Law)
The article evaluates the competences obtained by higher education students during their fulfilling certain scientific-research works. The evaluation allow to analyze the research competence of a student and presents an inseparable part of managerial cycle during its formation.